Web-Based 360 Virtual Tour Prototype Using the Waterfall Method: A Promotional Solution for Aura Boarding House in Riau Province - Nurul Qolbi; Abdullah (STMIK Methodist Binjai, 2026)
This study aims to design a web-based digital marketing platform prototype for the Aura Boarding House (kost putri) in Tembilahan, Riau, utilizing the Waterfall method and the Pannellum panorama viewer. The primary problem faced by the owner is suboptimal digital promotion despite its highly strategic location near campuses, schools, and community activity centers. The research methodology focuses on the system analysis and design phases. Requirement data were gathered through direct observation, informal interviews with the owner, and facility documentation using an iPhone 13 camera. The results of this design-phase study consist of system requirement documents, a one-page website structure, interface designs, a six-scene virtual tour storyboard, a booking procedure via Google Form integrated with Google Sheets, a monthly billing reminder blueprint via WhatsApp, and testing scenarios utilizing the black-box method. This study concludes that the marketing media design featuring a 360-degree virtual tour can deliver boarding house information transparently, clearly, and economically, serving as a concrete blueprint ready for full implementation in the subsequent thesis development stage